Marx's Discourse with Hegel - Levine, N. author. aut Link
VIII, 360 p.
Keywords: The end of Stalinist Russia, China's change under Deng Xiaoping and the publication of previously unexplored documents of Marx in the MEGA2 opened a new epoch in the analysis of Marx. Marx's Discourse With Hegel is both a product and contribution to this rebirth of Marxism by its reformulation of the relationship between Hegel and Marx.